Immunogenicity and safety of the adjuvanted recombinant zoster vaccine in adults with haematological malignancies: a phase 3, randomised, clinical trial and post-hoc efficacy analysis. Issue 9 (September 2019) - Dagnew, Alemnew F; Ilhan, Osman; Lee, Won-Sik; Woszczyk, Dariusz; Kwak, Jae-Yong; Bowcock, Stella; Sohn, Sang Kyun; Rodriguez Macías, Gabriela; Chiou, Tzeon-Jye; Quiel, Dimas; Aoun, Mickael; Navarro Matilla, Maria Belen; et al.
Summary: Background: The adjuvanted recombinant zoster vaccine (Shingrix) can prevent herpes zoster in older adults and autologous haemopoietic stem cell transplant recipients. We evaluated the safety and immunogenicity of this vaccine in adults with haematological malignancies receiving immunosuppressive cancer treatments. Methods: In this phase 3, randomised, observer-blind, placebo-controlled study, done at 77 centres worldwide, we randomly assigned (1:1) patients with haematological malignancies aged 18 years and older to receive two doses of the adjuvanted recombinant zoster vaccine or placebo 1–2 months apart during or after immunosuppressive cancer treatments, and stratified participants according to their underlying diseases. The co-primary objectives of the study were the evaluation of safety and reactogenicity of the adjuvanted recombinant zoster vaccine compared with placebo from the first vaccination up to 30 days after last vaccination in all participants; evaluation of the proportion of participants with a vaccine response in terms of anti-glycoprotein E humoral immune response to the adjuvanted recombinant zoster vaccine at month 2 in all participants, excluding those with non-Hodgkin B-cell lymphoma and chronic lymphocytic leukaemia; and evaluation of the anti-glycoprotein E humoral immune responses to the vaccine compared with placebo at month 2 in all participants, excluding those with non-Hodgkin B-cell lymphoma and chronic lymphocytic leukaemia. We assessed immunogenicity in the per-protocol cohort for immunogenicity and safety in the total vaccinated cohort. The study is registered with ClinicalTrials.gov, number NCT01767467, and with the EU Clinical Trials Register, number 2012-003438-18. Findings: Between March 1, 2013, and Sept 10, 2015, we randomly assigned 286 participants to adjuvanted recombinant zoster vaccine and 283 to placebo. 283 in the vaccine group and 279 in the placebo group were vaccinated. At month 2, 119 (80·4%, 95% CI 73·1–86·5) of 148 participants had a humoral vaccine response to adjuvanted recombinant zoster vaccine, compared with one (0·8%, 0·0–4·2) of 130 participants in the placebo group, and the adjusted geometric mean anti-glycoprotein E antibody concentration was 23 132·9 mIU/mL (95% CI 16 642·8–32 153·9) in the vaccine group and 777·6 mIU/mL (702·8–860·3) in the placebo group (adjusted geometric mean ratio 29·75, 21·09–41·96; p<0·0001) in all patients, excluding those with non-Hodgkin B-cell lymphoma and chronic lymphocytic leukaemia. Humoral and cell-mediated immune responses persisted above baseline until month 13 in all strata and, as expected, vaccine was more reactogenic than placebo (within 7 days after vaccination pain was reported by 221 [79·5%] of 278 vaccine group participants and 45 [16·4%] of 274 placebo group participants; fatigue was reported by 162 [58·3%] of 278 vaccine group participants and 102 [37·2%] of 274 placebo group participants). Incidences of unsolicited or serious adverse events, potential immune-mediated diseases, disease-related events, and fatal serious adverse events were similar between the groups. Interpretation: The immunocompromised adult population with haematological malignancies is at high risk for herpes zoster. The adjuvanted recombinant zoster vaccine, which is currently licensed in certain countries for adults aged 50 years and older, is likely to benefit this population. Funding: GlaxoSmithKline Biologicals SA.